Adaptive coupled diffusion model for vessel image enhancement. (22nd August 2011) - Zhao, Yongqiang; Li, Minglu; Ni, Jun
Based on the recently-developed crease enhancement diffusion (CED) filter, and combined the sharpening qualities of shock filters with excellent edge preservation and excellent smoothing for flat regions of total variation (TV) filter, an adaptive couple diffusion (ACD) filter is proposed to enhance the local coherence of vascular structures for medical images. This filter is tested on several experiments with synthetic and clinical images. The experimental results show the filter provides better performance for enhancement with further sharpening and denoising features.